Measuring the perceptual quality of pedestrian public space in contemporary Chinese cities – Taking Xinjiekou area in Nanjing as an example - Mawlan Muhetar; Xia Yue; Liang Gu; Huang Chenyi; Tang Lian (Lodz University of Technology Press, 2023)
One of the main goals of urban design is to obtain urban space with good perceptual qualities. Among the numerous perceptual qualities, enclosure, human scale, imageability, complexity, transparency, linkage, etc. are most related to the physical features (Ewing, Handy 2009) and many scholars use quantitative methods to measure these qualities. However, when applying these methods to measure these perceptual qualities of pedestrian public space in contemporary Chinese cities, there are problems as follows: first, the existing quantitative grading standards are very diverse and they are difficult to define accurately; second, for indoor pedestrian spaces, some indicators such as enclosure, imageability, etc. need to be re-identified. This paper selects the pedestrian public space in the Xinjiekou area in the center of Nanjing as an example. Based on the existing Nolli map of pedestrian public space (Luo et al. 2021), the enclosure, imageability, complexity, transparency, etc. are measured in a relatively more objective method. Firstly, streetscape photos of typical pedestrian public space (sidewalks, public squares, interior streets, etc.) are taken to a uniform standard. Secondly, street width, building height, number of people, signs, windows, types of elements, etc. in the streetscape are extracted to match enclosure, imageability, complexity, transparency and linkage, etc. Thirdly, the obtained evaluation results are verified by graphical representation and compared with similar studies. The research finally proposes graphical representation of perceptual qualities of pedestrian public space, which will help to optimize the urban design of space.
Keywords: urban design; pedestrian public space; perceptual quality; streetscape analysis; urbanistyka; piesza przestrzeń publiczna; jakość percepcyjna; analiza krajobrazu ulicznego